Pemberdayaan dan Tata Kelola Destinasi Pariwisata Desa Pentadu Timur Kecamatan Tilamuta Kabupaten Boalemo - Misran Rahman; Yakob Napu; Zulkarnain Anu (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2022)
This service aims to empower and manage tourism objects in the East Pentadu village, Tilamuta sub-district, Boalemo district. Some of the problems that arise in the management of these tourism objects need to find a way out. Through this service, it is hoped that the tourism awareness group will help in the promotion and management of the tourism object in the East Pentadu village. The method used in the workshop and focused discussion (Focus Discussion Group) which begins with the delivery of material by the resource person. Furthermore, discussions were held to produce several agreements on the management of tourism objects. The results of the service obtained agreements, including: (i) A more intense tourism promotion is needed in an effort to introduce tourism destinations in the village of East Pentadu, Tilamuta. (ii) Efforts to improve infrastructure are needed for access to destinations to tourist attractions. (iii) Efforts are needed to identify and improve the uniqueness of the area that becomes a tourist attraction.